Datafied female health: Sociotechnical imaginaries of femtech in Danish public discourse - Dahlman, Sara; Just, Sine N.; Munk Petersen, Linea; Valiant Lantz, Prins Marcus; Würtz Kristiansen, Nanna (MedieKultur: Journal of media and communication research, 2023)
The digitalization of health promises individual empowerment while raising the threat of collective surveillance. Conceptualizing these threats and promises as sociotechnical imaginaries, we explore how issues of datafied female health are articulated in Danish public discourse. Empirically, we work with a large data set of Danish news media coverage of algorithmic technologies in the past 10 years (2011–2021). We locate coverage of female-oriented health technologies (or femtech) by using the data sprint methodology to track the emergence of such technologies as a topic of public concern. Across the data, we identify two broad sociotechnical imaginaries: one zooming in on individual uses of femtech, the other focusing on the collective benefits of public health initiatives. We conclude that sociotechnical imaginaries of femtech are increasingly entangled in everyday life, making female bodies knowable through algorithms and data. As such, female health becomes subject to instrumental rationality, not lived reality.